The role of mTOR in age-related diseases - Zofia Chrienova; Eugenie Nepovimova; Kamil Kuca (Taylor & Francis Group, 2021)
The ageing population is becoming a significant socio-economic issue. To address the expanding health gap, it is important to deepen our understanding of the mechanisms underlying ageing in various organisms at the single-cell level. The discovery of the antifungal, immunosuppressive, and anticancer drug rapamycin, which possesses the ability to extend the lifespan of several species, has prompted extensive research in the areas of cell metabolic regulation, development, and senescence. At the centre of this research is the mTOR pathway, with key roles in cell growth, proteosynthesis, ribosomal biogenesis, transcriptional regulation, glucose and lipid metabolism, and autophagy. Recently, it has become obvious that mTOR dysregulation is involved in several age-related diseases, such as cancer, neurodegenerative diseases, and type 2 diabetes mellitus. Additionally, mTOR hyperactivation affects the process of ageing per se. In this review, we provide an overview of recent insights into the mTOR signalling pathway, including its regulation and its influence on various hallmarks of ageing at the cellular level.